2023
DOI: 10.3390/molecules28062502
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy for Early Detection of Cervical Cancer, a Global Women’s Health Issue—A Review

Abstract: This review focuses on recent advances and future perspectives in the use of Raman spectroscopy for cervical cancer, a global women’s health issue. Cervical cancer is the fourth most common women’s cancer in the world, and unfortunately mainly affects younger women. However, when detected at the early precancer stage, it is highly treatable. High-quality cervical screening programmes and the introduction of the human papillomavirus (HPV) vaccine are reducing the incidence of cervical cancer in many countries, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…15 Still playing an important role in the structural characterization of substances, this method has significantly expanded the scope of application. Nowadays, it is used for early detection of cancer, 16 bacteria detection, 17 to study the pathophysiology of brain diseases, 18 to determine the biochemical composition of plant, 19 etc. It also demonstrates the possibility of working with complex samples (multicomponent mixtures), for example, a study reported the classification of blood samples obtained from 11 animal classes and human subjects by statistical analysis of their Raman spectra.…”
Section: Discussionmentioning
confidence: 99%
“…15 Still playing an important role in the structural characterization of substances, this method has significantly expanded the scope of application. Nowadays, it is used for early detection of cancer, 16 bacteria detection, 17 to study the pathophysiology of brain diseases, 18 to determine the biochemical composition of plant, 19 etc. It also demonstrates the possibility of working with complex samples (multicomponent mixtures), for example, a study reported the classification of blood samples obtained from 11 animal classes and human subjects by statistical analysis of their Raman spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, novel screening techniques as well as methods for analysis could find their way from research uses to clinical applications in the near future. Because vibrational spectroscopy generates an individual molecular spectroscopic signature of tissues, it provides a quick, inexpensive, and non-destructive way for observer-independent tissue analysis [ 119 ]. It has been already successfully employed at a single-cell level to differentiate between normal cells and cells deriving from cervical intraepithelial neoplasia, using Raman spectroscopy on regular cervical cytology samples [ 120 ] as well as on tissue samples to distinguish between adenocarcinoma and squamous cell carcinoma [ 121 ] or among cervicitis, precursor lesions, and invasive carcinoma [ 122 ].…”
Section: The Future Of Cervical Cancer Screening—quo Vadimus?mentioning
confidence: 99%
“…Many commercially available Raman devices operate in a microscopic mode, allowing access to molecular information at the micrometric level under confocal conditions [ 30 , 31 ]. While Raman spectroscopy has been extensively studied in research for the mapping or profiling of biological tissues and cells for disease diagnosis and other biomedical applications [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ] or even subcellular analysis [ 39 , 40 , 41 ], it remains a powerful analytical technique. In the field of process analytical technology (PAT), Raman spectroscopy is used to monitor and control chemical and pharmaceutical processes [ 42 , 43 , 44 ], to predict end points of chemical synthesis reactions [ 45 ], and to track polymorphic changes in crystallisation processes [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%